The Three Faces of Populism in Power: Polity, Policies and Politics - Caiani, Manuela; Graziano, Paolo (Government and opposition (London), 2022)
In this article, we explore the consequences of the increasing presence of both left- and right-wing populist parties in government, critically reflecting on the recent scholarship on the topic, underlining promising venues for future research and outlining a conceptual framework which constitutes the background of this special issue entitled ‘Populism in Power and its Consequences’. Our main contribution is empirical, since – by reflecting on the various articles hosted in the special issue – we assess the impact of populist parties in government on politics, polities and various policy domains. We also provide an account of potential moderating factors of the influence of populists in government, focus on different ideological underpinnings of types of populisms (left-wing and right-wing) and discuss their relevance. We conclude by identifying four possible scenarios for European populist parties in governments: radicalization, compromise and moderation, splintering, or loss.